2013
DOI: 10.1177/0194599813495815a257
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Combined Furlow Palatoplasty and Sphincter Pharyngoplasty for Velopharyngeal Insufficiency

Abstract: Objectives: Compare surgical outcomes between pharyngeal flap, sphincter pharyngoplasty, and concomitant Furlow palatoplasty and sphincter pharyngoplasty in the management of pediatric velopharyngeal insufficiency. Methods: Retrospective review of 96 patients with velopharyngeal insufficiency, who underwent surgical intervention at a tertiary pediatric care center between 2008 and 2012. Patients with velocardiofacial syndrome were excluded from the study. Surgical interventions were categorized as pharyngeal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…On the other hand, a recent study showed that the sphincteroplasty combined with the Furlow technique, as well as the pharyngeal flap, were significantly more efficient in reducing hypernasality than the sphincteroplasty performed in isolation 28 . However, it is worth emphasizing that a limitation of this study was the fact that the authors employed only perceptual assessment of speech for analyzing results, without, however, evaluating concordance between examiners.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, a recent study showed that the sphincteroplasty combined with the Furlow technique, as well as the pharyngeal flap, were significantly more efficient in reducing hypernasality than the sphincteroplasty performed in isolation 28 . However, it is worth emphasizing that a limitation of this study was the fact that the authors employed only perceptual assessment of speech for analyzing results, without, however, evaluating concordance between examiners.…”
Section: Discussionmentioning
confidence: 97%
“…Among those surgical techniques employed in VPI treatment, pharyngeal flap and sphincteroplasty are still the most used in different craniofacial centers in the world 12,28,[32][33][34] and the literature has demonstrated the success and the deleterious effects of both these surgical techniques used in VPI treatment secondary to primary palatoplasty. Most studies used the perceptual methodology and/or direct instrumental methods for evaluation velopharyngeal function, such as nasoendoscopy and videofluoroscopy 12, [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a patient continues to have hypernasal speech, surgical repair is planned when the child is aged 3 or 4 years [1]. Numerous approaches to the surgical repair of VPI have been reported, including superior-based pharyngeal flap, sphincter pharyngoplasty, Furlow palatoplasty, and augmentation pharyngoplasty, and calcium hydroxylapatite or autologous fat injection [1][2][3][4]. Selection of which procedure(s) best suits each patient is highly individualized, taking into consideration suspected etiology, anatomic gap, age, syndromes, and many other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Complications documented in the literature include bleeding, aspiration, airway obstruction requiring reintubation/tracheotomy, flap dehiscence, and nasopharyngeal stenosis; however, the complication that has received the most attention is post-operative obstructive sleep apnea [1,4]. To our knowledge, respiratory failure has only been documented twice in recent literature and it was related to a central nervous system insult [5].…”
Section: Introductionmentioning
confidence: 99%